Rodinný dům s provozovnou - Vorlíčková, Petra (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tato bakalářská práce se zabývá návrhem novostavby rodinného domu s provozovnou. Obsahem je projektová dokumentace pro provedení stavby. Objekt se nachází v katastrálním území Lažánky u Blanska na svažité parcele. Dům je členěn na obytnou část určenou pro bydlení 4 osob a provozovnu – kadeřnictví. Obytná část je dvoupodlažní, z toho druhé podlaží tvoří klidovou zónu domu. Provozovna je umístěna v suterénu se samostatným vstupem i parkovacími místy. Díky umístění objektu do svahu je plně oddělena soukromá a veřejná část domu. Tvarově je objekt řešen jako samostatně stojící RD s obytným podkrovím ve 2 NP. Jedná se o monolitickou železobetonovou stavbu systému VELOX (ztracené tepelně izolační bednění), obdélníkového půdorysu. Zastřešena bude sedlovou střechou se sklonem 30° s betonovou skládanou krytinou.

This bachelor's thesis deals with the design of a new family house with an establishment. The content is the project documentation for construction work. The building is located in the cadastral area of Lažánky u Blanska on a sloping plot. The house is divided into a residential part intended for living of 4 persons and a shop - hairdressing. The residential part is a two-storey building, the second floor of which forms the quiet zone of the house. The plant is located in the basement with separate entrance and parking spaces. Due to the location of the object on the slope, the private and public part of the house is fully separated. The building is designed as a detached house with a residential attic in 2 NP. It is a monolithic reinforced concrete structure of the VELOX system (a lost thermal insulation formwork), a rectangular ground plan. It will be roofed with a saddle roof with a 30 ° inclination with a concrete folded cover.
Family house with an establishment
Keywords: Rodinný dům s provozovnou; sedlová střecha; systém VELOX; svah; Family house with an establishment; saddle roof; VELOX system; slope